Viabilitas Lactobacillus plantarum 1 Yang Diisolasi Dari Susu Kedelai Terfermentasi Spontan Terhadap Asam Klorida dan Garam Empedu - Elisa Apridani; Yusmarini '; Rahmayuni ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2014)
Most of probiotic isolate is from overseas therefore it needs effort to obtain probiote acid lactid bacteria indigenus.Thepurposeof the research was to obtain viability of Lactobacillus plantarum 1 that isolated from spontaneous fermented soymilk on acid chloride and oxgall. This research used isolate of Lactobacillus plantarum 1 R.11.1.2, Lactobacillus plantarum 1 R.1.3.2,Lactobacillus acidophilus FNCC 0051 and Streptococcus thermophilus FNCC 0040 on medium addition with chloride acid at pH 4, 3, and 2 and addition with oxgall 0.5%.The result showed thatL. plantarum1 R.11.1.2and L.plantarum 1 R.1.3.2 was survive and able to grow on pH 4 during 5 hours incubation.Lactobacillus plantarum1 R.11.1.2andL. plantarum 1 R.1.3.2was survive at pH 3 during 5 hours incubation. Lactobacillus plantarum1 R.11.1.2andL. plantarum 1 R.1.3.2 was unable to survive on pH 2 during neither 2.5 hours nor 5 hours incubation. Lactobacillusplantarum1 R.11.1.2and L.plantarum 1 R.1.3.2 was able to survive on medium with oxgall 0.5%. Keywords: Viability, Lactobacillus plantarum 1, ChlorideAcid, Oxgall